A Randomized Controlled Trial to Optimize Indocyanine Green‐Augmented Diode Laser Therapy of Capillary Malformations. Issue 4 (26th April 2013) - Klein, Annette; Bäumler, Wolfgang; Buschmann, Marius; Landthaler, Michael; Babilas, Philipp
Abstract Background Indocyanine green (ICG)‐augmented diode laser therapy (ICG + DL) represents a new treatment modality for capillary malformations (CM). However, an increase of the ICG‐concentration or the use of an intense pulsed light (IPL) device as light source may further optimize treatment outcomes in CM. Objective : This proof‐of‐concept trial including 15 patients (skin type II to III) with CM evaluated the efficacy and safety of ICG‐augmented diode laser therapy (808 nm) at a total dose of 4 mg/kg body weight (b.w.). Additionally, five patients with extensive CM received IPL therapy before and after ICG‐administration (ICG + IPL). Methods ICG was intravenously administered to 15 patients with CM at a total dose of 4 mg/kg b.w. Immediately after ICG injection, diode laser pulses with different radiant exposures (20–110 J/cm2) were applied as one single treatment. Five patients with extensive CM additionally received IPL (555–950 nm) therapy. Safety and efficacy were assessed both 1 and 3 months after the single treatment by a blinded investigator and the patient. Furthermore, color of the CM was objectively measured by means of a color meter (colorStriker™, Eduard Mathai GmbH, Hannover, Germany). Treatment with the flashlamp‐pumped pulsed dye laser (FPDL) and the IPL alone (five patients) served as reference treatment. Results According to the assessment by the patients and the blinded investigator, the clearance rate was slightly better after ICG + DL therapy than after FPDL treatment (P = 0.1, P = 0.8). In one out of five patients, IPL with and without ICG injection induced poor to moderate clearance of CM and persisting erythema in another patient. The correlation between the visual assessment by the blinded investigator and the colorimetric measurements was poor. Conclusion A minority of patients with CM may benefit from ICG + DL therapy, but efficacy cannot be improved by higher ICG doses. Lasers Surg. Med. 9999:XX–XX, 2013. © 2013 Wiley Periodicals, Inc.